Force-Fighting Phenomena and Disturbance Rejection in Aircraft Dual-Redundant Electro-Mechanical Actuation Systems - Young Tak Han; Sang-Duck Im; Bongsu Hahn (Actuators, 2023)
This paper presents a robust control system that addresses two key challenges in redundant actuators using Permanent Magnet Synchronous Motors (PMSM) for an aircraft nose wheel steering system: the elimination of force-fighting phenomena and the ability to respond effectively to unexpected disturbances. In detail, a control method was devised to enhance the mitigation of force-fighting phenomena and disturbances by accurately observing and compensating for the torque-induced load applied to the PMSM. This was achieved through the utilization of a Q-filter-based Disturbance Observer (DOB). The proposed control approach was implemented and evaluated on a redundant system consisting of the PMSM and the nose wheel steering system. The performance of the proposed method was verified through extensive simulation studies. The simulation results confirmed the effectiveness and reliability of the method in accurately observing and responding to the force-fighting phenomenon that occurs in the redundant driving device. By subjecting the system to various scenarios and disturbances, the simulation provided a comprehensive evaluation of the proposed method’s ability to handle force-fighting phenomena. The results demonstrated that the method successfully observed and responded to the force-fighting phenomenon, thereby mitigating its adverse effects on the system’s performance. Therefore, these outcomes serve as empirical evidence supporting the validity and efficiency of the proposed method in addressing the force-fighting phenomenon encountered in the redundant driving device. These findings substantiate the effectiveness of the proposed approach and its potential for practical implementation in real-world systems.